A Multi-User Terminology Mapping Toolbox - Mate, Sebastian; Seuchter, Susanne A.; Ehrenberg, Katharina; Deppenwiese, Noemi; Zierk, Jakob; Prokosch, Hans-Ulrich; Kraska, Detlef; Kapsner, Lorenz (German Medical Data Sciences: Bringing Data to Life, 2021)
Semantic interoperability is a major challenge in multi-center data sharing projects, a challenge that the German Initiative for Medical Informatics is taking up. With respect to laboratory data, enriching site-specific tests and measurements with LOINC codes appears to be a crucial step in supporting cross-institutional research. However, this effort is very time-consuming, as it requires expert knowledge of local site specifics. To ease this process, we developed a generic manual collaborative terminology mapping tool, the MIRACUM Mapper. It allows the creation of arbitrary mapping workflows involving different user roles. A mapping workflow with two user roles has been implemented at University Hospital Erlangen to support the local LOINC mapping. Additionally, the MIRACUM LabVisualizeR provides summary statistics and visualizations of analyte data. We developed a toolbox that facilitates the collaborative creation of mappings and streamlines the review as well as the validation process. The two tools are available under an open source license.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Interoperability; Laboratory; LOINC; Secondary Use; Terminology